1988
DOI: 10.1007/bf00844288
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytoskeletal proteins in basal cells of human parotid salivary gland ducts

Abstract: From previous immunofluorescent, immunohistochemical and ultrastructural studies, myoepithelial cells have been reported to be absent from the striated and excretory ducts of human salivary gland. Yet recently, certain anti-cytokeratin monoclonal antibodies which specifically label the myoepithelium of salivary gland acini and intercalated ducts have also been found to stain basally situated cells in both striated and excretory ducts. In this study, we have used eight samples of normal human parotid gland (met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…As duct-like and /or myoepitheliallike cells are the predominant histopathological features of salivary neoplasms, a subpopulation of ductal cells located on the non-luminal aspect of the striated and excretory ducts of human salivary glands with a more heterogeneous and functionally more complex features have been identified by ultrastructural and immunohistochemical studies [7], which in the present study showed consistent immunoreactivity for MT. These cells termed as the ductal basal cells, their nature and function not fully clear at present, have been suggested to share numerous common immunohistochemical markers with the myoepithelial cells and at least some of the ductal basal cells may serve as the progenitor-reserve cells of salivary gland neoplasms, if not all [7,8]. However, in salivary tumors, there is no direct evidence for genesis of neoplastic myoepithelial cells either from the myoepithelial cell itself nor from ductal basal cells.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As duct-like and /or myoepitheliallike cells are the predominant histopathological features of salivary neoplasms, a subpopulation of ductal cells located on the non-luminal aspect of the striated and excretory ducts of human salivary glands with a more heterogeneous and functionally more complex features have been identified by ultrastructural and immunohistochemical studies [7], which in the present study showed consistent immunoreactivity for MT. These cells termed as the ductal basal cells, their nature and function not fully clear at present, have been suggested to share numerous common immunohistochemical markers with the myoepithelial cells and at least some of the ductal basal cells may serve as the progenitor-reserve cells of salivary gland neoplasms, if not all [7,8]. However, in salivary tumors, there is no direct evidence for genesis of neoplastic myoepithelial cells either from the myoepithelial cell itself nor from ductal basal cells.…”
Section: Discussionsupporting
confidence: 74%
“…A consistent reactivity of MT in salivary tumors in non-luminal cells, the neoplastic myoepithelial cells or their counterparts, in particular, in the majority of the salivary tumors evaluated in the present study may have a potential implication in defining the role of neoplastic myoepithelial cells, believed by many investigators to have a major role in the histomorphology and histogenesis of salivary tumors [9]. As duct-like and /or myoepitheliallike cells are the predominant histopathological features of salivary neoplasms, a subpopulation of ductal cells located on the non-luminal aspect of the striated and excretory ducts of human salivary glands with a more heterogeneous and functionally more complex features have been identified by ultrastructural and immunohistochemical studies [7], which in the present study showed consistent immunoreactivity for MT. These cells termed as the ductal basal cells, their nature and function not fully clear at present, have been suggested to share numerous common immunohistochemical markers with the myoepithelial cells and at least some of the ductal basal cells may serve as the progenitor-reserve cells of salivary gland neoplasms, if not all [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…In the ductal epithelium of normal salivary glands, the antibodies K8.12, PKK1 and KL1 were reactive with the luminal and basal cells in the intercalated, striated and excretory ducts with different reaction intensities. The immunoreactivity of antibody K8.12 was predominantly present in the basal cells, while that of antibodies PKK1 and KL1 was equally present in the luminal and basal cells [3,8,29,39,41]. In prenatally developing salivary glands, ductal basal cells have been found to be similar to those found in the adult glands with respect to the expression of cytokeratins detected by antibodies K8.12 and PKK1 which appears relatively early during the differentiation of larger ducts [21].…”
Section: Discussionmentioning
confidence: 77%
“…The cytokeratins detected by antibodies K8.12, PKK1 and KL1 have been consistently demonstrated in normal and neoplastic lesions of the salivary glands [3,8,12,23,39,41]. In the ductal epithelium of normal salivary glands, the antibodies K8.12, PKK1 and KL1 were reactive with the luminal and basal cells in the intercalated, striated and excretory ducts with different reaction intensities.…”
Section: Discussionmentioning
confidence: 90%
“…The subpopulation of ductal cells located on the abluminal aspect of excretory and striated ducts of human major and minor salivary glands with a more heterogeneous and functionally more complex features have been identified by ultrastructural and immunohistochemical studies [42] . These cells have been termed as ductal basal cells but studies on their nature and function, not fully clear at present, have suggested that they share numerous common immunohistochemical markers with the myoepithelial cells and at least some of the ductal basal cells, if not all, may serve as the progenitor-reserve cells of salivary gland neoplasms [116].…”
Section: IIImentioning
confidence: 99%